2011
DOI: 10.1016/j.accfor.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The accounting treatment of intangibles – A critical review of the literature

Abstract: a b s t r a c tIntangible investments have become the main value creators for many companies and economic sectors. However, these investments are rarely recognized as assets by current accounting standards. We provide a critical review of the literature on the consequences of this lack of accounting recognition of intangibles for the value-relevance of financial information, resource allocation in the capital market, growth of intangible investments, and the firm's market value. We then review recent empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 61 publications
2
70
0
8
Order By: Relevance
“…Despite all the interest in this concept, a plethora of terminologies are used in discussing the intellectual capital in the literature (Zeghal & Maaloul, 2011). Terms generally used are "intangibles", "intangible assets", "knowledge assets", "intellectual capital", "intangible capital" "intellectual assets" "intangible resources" and "knowledge resources".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all the interest in this concept, a plethora of terminologies are used in discussing the intellectual capital in the literature (Zeghal & Maaloul, 2011). Terms generally used are "intangibles", "intangible assets", "knowledge assets", "intellectual capital", "intangible capital" "intellectual assets" "intangible resources" and "knowledge resources".…”
Section: Introductionmentioning
confidence: 99%
“…Like many researchers in financial accounting, we will consider in this study, the term "intellectual capital" as the set of elements not taken into account in accounting. In order to compensate the loss of relevance of financial information, several researchers in this field have presented the voluntary disclosure of information on intangibles as the solution (Zeghal & Maaloul, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, our most significant contribution to JAAR 17,4 this research is the investigation of the role of intangible narrative information in the analysts' earnings forecasts' properties. It is well known that information about intangibles is not fully and completely integrated into financial statements (AAA Financial Accounting Standards Committee, 2003;Zeghal and Maaloul, 2011). Narrative disclosures about those intangibles in annual reports may represent an important source of information that is potentially useful to financial analysts.…”
Section: Introductionmentioning
confidence: 99%
“…The current accounting treatment of intangibles may have adverse socio-economic consequences for firms, financial markets, and society in general (AAA Financial Accounting Standards Committee, 2003;Zeghal and Maaloul, 2011). From the investors' perspective, prior studies show that the non-recognition of intangibles exacerbates information asymmetry between a firm's insiders and outsiders (Aboody and Lev, 2000), resulting in a firm's mis-valuation (Lev et al, 2005), making firm shares relatively illiquid (Boone and Raman, 2001), and increasing its cost of capital (Seow et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ownership rights, goodwill), it is necessary to report or obtain more comprehensive (non-financial, forward-looking) information about it/them somewhere else. It has been shown that disclosures significantly supplement companies' financial statements or are, as stated by Zéghal and Maaloul (2011), "considered as a solution to the negative consequences of non-recognition of intangibles in financial statements." Intellectual capital disclosures are almost exclusively voluntary; they can be given separately or within some other (public) reporting (e.g.…”
Section: Introductionmentioning
confidence: 99%